Trans Fatty Acids and Cardiovascular Disease Risk - Elisaf, M. S.; Georgoula, M.; Filippatos, T. D.; Liontos, A. M. (Journal of Nutritional Therapeutics, 2014)
Trans fatty acids (TFA) are fatty acids that contain at least one double bond that is in the trans configuration. TFA are consumed mainly with industrial partially hydrogenated vegetable fats that are used in the production of margarines and “shortenings”. The consumption of ruminant TFA provide another source of TFA in European countries. TFA consumption generally increases total cholesterol and decreases high density lipoprotein cholesterol and is associated with increased risk of cardiovascular disease. The results of some large-scale epidemiological studies suggest that the increased cardiovascular disease risk with the consumption of TFA is possibly greater than would be predicted from changes in plasma lipid levels alone. The experience from different countries shows that the elimination of TFA is a cost effective and feasible public health intervention. Based on the scientific evidence, the consumption of TFA should be further targeted aiming to further reduce of TFA in fast food products and the implementation of newer industrial methods that produce vegetable oils with lower (or even zero) amounts of TFA.